Penggunaan Media WhatshApp pada Pembelajaran Maharah Kalam Bahasa Arab pada Mahasiswa PBA IAI Al-Qodiri Jember - Ainul Yaqin, Muhammad (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Online Arabic classes, including maharah kalam, are available. This circumstance prevents pupils from meeting offline and makes it tough for them to hold an Arabic conversation. One of these is to use the simple Whatsapp messaging service, which everyone has on their phones. This is a qualitative descriptive research. The goal of this study is to define WhatsApp as a learning media maharah kalam. Interviews, observation, and documentation were used to gather information. The findings of this study show that learning mahrah kalam via WhatsApp during this online period might improve communication between instructors and students, as well as amongst students who are conversing in Arabic. Furthermore, various tools present in the WhatsApp medium, particularly the voice note and video call functions, assist in learning Maharah Kalam. Keywords: Learning Media; Whatsapp; Maharah Kalam.